2022
DOI: 10.1017/s0007114522000563
|View full text |Cite
|
Sign up to set email alerts
|

Association between healthy lifestyle pattern and early onset of puberty: based on a longitudinal follow-up study

Abstract: The present study aimed to explore the association between healthy lifestyle pattern and childhood early onset of puberty. Based on a cohort study in Xiamen of China, a total of 1294 children was followed for three and a half years. Children’s lifestyles, including dietary behavior, physical activity, sleep duration, smoking and drinking behavior, and sedentary behavior, were collected by questionnaires. Healthy lifestyle pattern was determined mainly according to the recommendations by the Dietary Guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Similar to the results of this study, the difference in overweight and obesity between urban and rural areas of Chinese children and adolescents also found a decreasing trend over time [49]. It is essential to promote a healthy lifestyle and counteract the prevalence of obesity, especially among rural children and adolescents [50,51].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the results of this study, the difference in overweight and obesity between urban and rural areas of Chinese children and adolescents also found a decreasing trend over time [49]. It is essential to promote a healthy lifestyle and counteract the prevalence of obesity, especially among rural children and adolescents [50,51].…”
Section: Discussionsupporting
confidence: 81%
“…Some investigators found that girls who started puberty early tended to reach menarche rapidly (9,10), but the interval from Tanner stage B2 to peak height velocity was longer for early maturing girls than that of average or late maturing girls (10). In contrast, Li et al found no evidence for an association between timing and tempo in Chinese girls (11), and Marceau et al suggested that timing and tempo were associated in boys, but not in girls (12).…”
mentioning
confidence: 98%
“…Many countries imposed restrictions on flights from China, movement, and social contact, as well as visitors from high-risk areas were required to be quarantined (Coronavirus, 2020).Individuals, particularly children, were highly likely to spend more time at home due to the lockdown mandated by the governments of several countries, including Pakistan, Brazil, India, Turkey and China affecting their daily routine significantly (Ali et al, 2022;Barberi et al, 2022;Prosperi & Chiarelli, 2022). Lifestyle changes, such as dietary habits and sleep schedules, can have a substantial impact on a child's sexual development, including the initiation of puberty (Li et al, 2022).…”
mentioning
confidence: 99%